Case study -- reducing pesticide residues on horticultural crops: food safety in food security and food trade - Norton, George W.; Sanchez, Guillermo E.; Clarke-Harris, Dionne; Kone Teaore, Halimatou (International Food Policy Research Institute, 2003)
Production and export of horticultural products are increasing rapidly in many developing countries... Rapid growth in horticultural production has been accompanied by heavy use of pesticides and by heightened concern over health effects associated with pesticide use and abuse...The three examples [in this study] demonstrate how applied research to support IPM can reduce pesticide use, residues, and export barriers. -- from Text